Software for the Diagnosis of Accumulated Stock of Social Capital in the Business Context. An Alternative to Business Development (GEON Journal (Management, Organizations and Business), 2017)
Participation in networking is an alternative to generate greater competitiveness in the business context, so that the development of social capital based on the recognition of social values becomes a necessary step to promote cohesion within organizations input. Social capital as an intangible asset of a community or cluster, is based on the recognition of the social structure, which from the associativity produces public and private benefits. Structuralism as an epistemological foundation of capital from sociology identifies the elements that legitimizes networks to exist; however, one can not say that the capital is limited to networks only because it involves an intangible cognitive dimension of social values such as trust and reciprocity. In the case of this project it is working on creating a tool to devise strategies to strengthen the social capital within organizations from recognition of cognitive and structural dimensions, in order to generate interaction with other organizations and likewise strengthen relations. In this sense, a software to measure the capacity to generate capital within each organization is proposed. Software development will take place and finally implemented in medium-sized enterprises, it shall be based on a methodology based on the process lifecycle of an information system.
Keywords: Software; Closed capital; Associativity; Social Values; Information System